Formulasi Strategi Pembinaan Remaja Masjid Al-Falah Kelurahan Latsari Tuban - Yayah Komariyah; Ahmad Khairul Hakim (Journal of Islamic Management, 2021)
The problem examined by this study is how the process strategy planning in the founding of Islamic Youth of Al-Falah Mosque in Latsari Tuban and what the content of planning the founding strategy. The research aims to illustrate how the Islamic Youth of Al-Falah Mosque in Latsari Tuban does to prepare strategy planning in the founding of Islamic youth and also to find out the content of planning the founding strategy. To describe that two problems, researcher used a qualitative method with case study. The data was dig deep with interview techniques, observation, and documentation. The research provided the following results. First, in strategy planning process, the Islamic Youth of Al-Falah Mosque used external analysis, then formulated vision for the next five years, discussion with core functionaries, then rediscuss to all of organization’s devisions and praying together. Second, the design of Islamic Youth founding strategy was that there was a formulation of a target program of activities, measuring activity program’s and also developes the activity by adding new activity programs.